Half-mode substrate integrated waveguide antenna for generating multiple orbital angular momentum modes - Chen, Yiling; Zheng, Shilie; Chi, Hao; Jin, Xiaofeng; Zhang, Xianmin (Electronics letters, 2016)
To multiplex multiple orbital angular momentum (OAM) beams, a compact half-mode substrate integrated waveguide leaky-wave antenna (LWA) for generating multiple high-order OAM modes is presented. The LWA is based on a cavity resonator with two feeds of ±90° phase difference. The principle and mode analysis of the resonator are discussed, and the generation of high-order OAM beams is proved by the measurements.